2015
DOI: 10.15740/has/ijas/11.1/138-140
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the effect of pre-harvest application of plant growth regulators and chemicals on yield and quality of guava (Psidium guajava L.) cv. L.-49

Abstract: A field experiment to study the effect of pre-harvest application of plant growth regulators and chemicals namely giberellic acid, naphthalene acetic acid, calcium chloride, zinc sulphate, potassium sulphate and control on yield and post harvest quality of guava (Psidium guajava L. cv. L.-49

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…The higher sugar content of fruits might be due to role of potassium in translocation of sugars from leaves to fruits and maybe be because of higher assimilating power of leaves over a long period resulting in increased availability of sugars in the fruits. These results are similar with Hamouda et al, (2015) and Tehranifar and Tabar (2009) in pomegranate, Vijayalakshmi and Srinivasan (2000), Kumar et al, (2006) and Baiea et al, (2015) in mango, Manivannan et al, (2015) and Dutta (2004) in guava, Nandan et al, (2011) in banana, Pandey and Singh (2016) in litchi, Doroshenko et al, (2005) in apple and Lester et al, (2007) in cantaloupe. The results gained in the present investigation under different potassium sources found significant concerning juice pH, ascorbic acid and anthocyanin content (Table 3).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The higher sugar content of fruits might be due to role of potassium in translocation of sugars from leaves to fruits and maybe be because of higher assimilating power of leaves over a long period resulting in increased availability of sugars in the fruits. These results are similar with Hamouda et al, (2015) and Tehranifar and Tabar (2009) in pomegranate, Vijayalakshmi and Srinivasan (2000), Kumar et al, (2006) and Baiea et al, (2015) in mango, Manivannan et al, (2015) and Dutta (2004) in guava, Nandan et al, (2011) in banana, Pandey and Singh (2016) in litchi, Doroshenko et al, (2005) in apple and Lester et al, (2007) in cantaloupe. The results gained in the present investigation under different potassium sources found significant concerning juice pH, ascorbic acid and anthocyanin content (Table 3).…”
Section: Resultssupporting
confidence: 89%
“…The results were in line with Heshi et al, (2001), Khayyat et al, (2012), Thirupathi and Ghosh (2015) and Hamouda et al, (2015) in pomegranate, Dalal et al, (2017) and Vijay et al, (2016) in sweet orange cv. Jaffa, Manivannan et al, (2015) in guava, Altindisli et al, (1999) in grapes, Yadav et al, (2014) in berand Baiea et al, (2015) in mango. Also, it was reported that a positive correlation exists between potassium concentration and anthocyanin content which play a crucial role in anthocyanin synthesis through increasing the translocation of sugars into fruits, as well as acting as a cofactor and stimulator of some enzymes like UDPgalactose: flavonoide-3-o-glicosyl transferase.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Agnihotri et al (2013) [2] found that foliar spraying with 60 ppm 2, 4-D increased shoot length. The usage of potassium sulphate (1%) significantly improved the branch length of the guava tree (Manivannan et al, 2015) [54] . According to Bhagawati et al (2015) [9] , the earliest emergence of buds and cumulative lengths of new shoots are due to vigorous pruning.…”
Section: Effect On Linear and Radial Growth Of Shootmentioning
confidence: 99%
“…According to Katiyar et al (2009) [44] , the maximum yield was found in urea 2% + NAA 100 ppm. Manivannan et al (2015) [54] investigated that application of potassium sulphate (1%) significantly enhanced the yield parameters viz., fruit length, number of fruits, fruit weight and yield per tree. Saini et al (2016) [71] observed that all the treatments were effective in increasing the growth characters, however, heading back at the level of 200 cm and two pinchings were found most effective in increasing the growth characters i.e.…”
Section: Fruit Yieldmentioning
confidence: 99%